2006
DOI: 10.1111/j.1442-200x.2006.02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mesenteric involvement with plexiform neurofibroma in neurofibromatosis type 1

Abstract: Key wordsintestinal mesentery , neurofi bromatosis type 1 , plexiform neurofi broma .Correspondence: Mustafa I ˙m amo g lu,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Intestinal plexiform neurofibromas present with ulceration, bleeding, intestinal obstruction, and rarely, intussusception, volvulus, and perforation. Intestinal vascular and lymphatic obstruction may result in bowel edema, loss of protein-rich chyle into the bowel lumen, causing hypoproteinemia and malabsorption [4,5,10]. However, most small mesenteric plexiform neurofibromas are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal plexiform neurofibromas present with ulceration, bleeding, intestinal obstruction, and rarely, intussusception, volvulus, and perforation. Intestinal vascular and lymphatic obstruction may result in bowel edema, loss of protein-rich chyle into the bowel lumen, causing hypoproteinemia and malabsorption [4,5,10]. However, most small mesenteric plexiform neurofibromas are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal involvement occurs in about 10% to 25% of patients with NF-1 and includes solitary or multiple neurofibromas, leiomyomas, and rarely, plexiform neurofibromas [2]. Although several cases of mesenteric neurofibroma have been reported in the pediatric populations, involvement of the mesentery and mesorectum has not been previously reported [1,[3][4][5][6][7].…”
mentioning
confidence: 99%
“…Suspicious clinical features for malignant transformation include increased rate of growth of a portion or entire tumor and the occurrence of spontaneous pain not explained by trauma [4]. In such cases, biopsy should be performed to exclude malignant transformation [21].…”
Section: Ah Mansour Et Al / Genitourinary Plexiform Neurofibromamentioning
confidence: 99%
“…Clinically, neurofibromas cause no symptoms in the majority of patients with NF1 [2]. Therefore, periodic clinical and radiological monitoring should be performed for early diagnosis of insidious involvement [21], as this may decrease a patient's morbidity and improve the chances of complete excision [1].…”
Section: Ah Mansour Et Al / Genitourinary Plexiform Neurofibromamentioning
confidence: 99%
“…In the genitourinary region, Nguyen et al [5] reported that NF in two children who presented with recurrent urinary tract infection caused massive bilateral hydroureteronephrosis and a thick-walled bladder due to obstruction caused by compression of the mass. In the review of Imamoglu et al [4], they concluded that NF also arise possibly from intestinal mesenteric (autonomic nerve fibres accompanying the mesenteric blood vessels) nerves, and may present a history of vague abdominal symptoms, including intermittent abdominal pain and failure to thrive.…”
mentioning
confidence: 99%